2002
DOI: 10.1111/1467-8624.00435
|View full text |Cite
|
Sign up to set email alerts
|

The Relation between Children's and Mothers’ Mental State Language and Theory‐of‐Mind Understanding

Abstract: This study investigated the relation between mothers' utterances and theory of mind in a longitudinal study involving three time points over 1 year. Mothers were asked to describe some pictures to 82 children at all three time points. Mothers' use of mental state utterances in these descriptions at early time points was consistently correlated with later theory-of-mind understanding. This was true even when a number of potential mediators were accounted for, including children's own use of mental state languag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

45
684
10
33

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 714 publications
(772 citation statements)
references
References 46 publications
45
684
10
33
Order By: Relevance
“…Longitudinal and cross-sectional studies have shown that the more a mother uses mental-state terms when speaking to her child, the better the child's understanding of false belief Symons, Fossum, & Collins, 2006) and of emotion (Taumoepeau & Ruffman, 2008;Wang, Doan, & Song, 2010) and the more frequently the child itself makes use of psychological lexicon (Howard, Mayeux, & Naigles, 2008;Scholnick & Hall, 1991). Other research with preschool children has indicated an association between the frequency with which they use mental-state terms during spontaneous conversation and their scores on false-belief ToM tasks (Brown, Donelan-McCall, & Dunn, 1996;Hughes, Lecce, & Wilson, 2007;Ornaghi & Grazzani Gavazzi, 2009;Ruffman et al, 2002;Symons, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Longitudinal and cross-sectional studies have shown that the more a mother uses mental-state terms when speaking to her child, the better the child's understanding of false belief Symons, Fossum, & Collins, 2006) and of emotion (Taumoepeau & Ruffman, 2008;Wang, Doan, & Song, 2010) and the more frequently the child itself makes use of psychological lexicon (Howard, Mayeux, & Naigles, 2008;Scholnick & Hall, 1991). Other research with preschool children has indicated an association between the frequency with which they use mental-state terms during spontaneous conversation and their scores on false-belief ToM tasks (Brown, Donelan-McCall, & Dunn, 1996;Hughes, Lecce, & Wilson, 2007;Ornaghi & Grazzani Gavazzi, 2009;Ruffman et al, 2002;Symons, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…One of the aspects investigated is the correlation between maternal mental language and ToM development (Dunn, Brown, & Beardsall, 1991;Ruffman, Slade & Crowe, 2002). Longitudinal and cross-sectional studies have shown that the more a mother uses mental-state terms when speaking to her child, the better the child's understanding of false belief Symons, Fossum, & Collins, 2006) and of emotion (Taumoepeau & Ruffman, 2008;Wang, Doan, & Song, 2010) and the more frequently the child itself makes use of psychological lexicon (Howard, Mayeux, & Naigles, 2008;Scholnick & Hall, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…In longitudinal studies, forms of family talk about mental states have been found to be related to later success on false belief tests (e.g., Brown et al 1996;Dunn et al 1991a;Ruffman et al 2002). In addition, mothers who think of their children in mentalistic terms ("mindmindedness"), and therefore, presumably talk to their children about the psychological world, have children who are more advanced in understanding beliefs than are other children (Meins & Fernyhough 1999;Meins et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…"Are you angry?" The social process suggested by C&L is clearly central to the development of such content knowledge (Jenkins et al 2003;Ruffman et al 2002).Prioritization of joint goals. Only if one cares enough about the internal experiences of others can the joint goal achieve prominence over one's own goals.…”
mentioning
confidence: 99%
“…Behavior analysts generally view perspective taking as a learned repertoire (Barnes-Holmes, McHugh, BarnesHolmes, & Barnes-Holmes, 2004). In a global sense, this idea is supported by the growing body of research showing that perspective-taking skills are influenced by environmental factors, such as the presence of siblings (e.g., Cassidy, Fineberg, Brown, & Perkins, 2005), family size (e.g., Jenkins & Astington, 1996), the relative age and gender of siblings (e.g., Ruffman, Perner, Naito, Parkin, & Clements, 1998), and the quality of sibling and maternal conversations about perspective taking (e.g., Foote & Homes-Lonergan, 2003;Peterson & Slaughter, 2003;Ruffman, Slade, & Crowe, 2002).…”
mentioning
confidence: 99%